2018
DOI: 10.1186/s13046-018-0723-5
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the effect of first line treatment in RAS/RAF mutated metastatic colorectal cancer by serial analysis of tumor specific DNA in plasma

Abstract: BackgroundPrecision medicine calls for an early indicator of treatment efficiency. Circulating tumor DNA (ctDNA) is a promising marker in this setting. Our prospective study explored the association between disease development and change of ctDNA during first line chemotherapy in patients with RAS/RAF mutated metastatic colorectal cancer (mCRC).MethodsThe study included 138 patients with mCRC receiving standard first line treatment. In patients with RAS/RAF mutated tumor DNA the same mutation was quantified in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 28 publications
1
38
0
Order By: Relevance
“…2 e, we found that an early decrease in cfDNA concentration was related to a good therapeutic effect. Thomsen et al also reported that a low level of cfDNA after chemotherapy, prior to radiological imaging evaluation, was associated with a low risk of progression [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…2 e, we found that an early decrease in cfDNA concentration was related to a good therapeutic effect. Thomsen et al also reported that a low level of cfDNA after chemotherapy, prior to radiological imaging evaluation, was associated with a low risk of progression [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…An early decrease in cfDNA concentration was related to a good therapeutic effect. Thomsen et al reported that a low level of cfDNA after chemotherapy, prior to radiological imaging evaluation, was associated with a low risk of progression [24] .…”
Section: Discussionmentioning
confidence: 99%
“…An early decrease in cfDNA concentration was related to a good therapeutic effect. Thomsen et al reported that a low level of ctDNA after chemotherapy, prior to radiological imaging evaluation, was associated with a low risk of progression [18] .…”
Section: Discussionmentioning
confidence: 99%